Análise da espacialização dos homicídios na cidade de Uberlândia/MG - Santos, Márcia Andréia Ferreira (2006)
This study makes an approach of the homicide occurrences at Uberlândia city (MG) in the years among 2000 and 2003. The research presents the discussions about the violence and criminality realized by diverse areas of the scientific knowledge: Geography, Anthropology, Sociology and Public Health. During the study, the following methodological procedures had been made: 1) bibliographical survey and revision; 2) survey of information on research groups directed to the violence thematic; 3) survey of the works on violence presented in Geography scientific events; 4) survey of thesis and dissertations about violence, defended in Geography Pos-Graduate Programs; 5) research of data in governmental institutions; 6) selection of the variable to be studied (economic, social and criminal, related to the homicides); 7) choice of the institutions in which would be collected the information; 8) analysis of news articles of the periodical Jornal Correio on security and violence in Uberlândia; 9) interviews with inhabitants and agents of the PISC; 10) systematization of the data in form of graphs, tables, pictures and maps, and analysis of the same ones. To analyze the victim profile, the geographic space of occurrence and the circumstances in which this events happened, we had been selected the following variable: sex, age group, skin colour, marital status, place of the death occurrence, place of the event occurrence, instrument used (weapon) to produce the homicide, day of the week, moment of the occurrence (hour), the traffic presence and drugs use in the quarters of the city. We realized correlative analyses between the homicides and two social-economic variables: income and schooling. The results reached in the analysis of the homicides in Uberlândia had been the following facts: 90% of the victims were masculine sex; 37% had age between 20 and 29 years old; 64% were white color, 62% were single; 39% had died in hospitals; 60% of the homicides had been practiced using firearms; the majority of the homicides (22%) occurs in the Sunday; 32% of the events homicides had been registered in the interval of time between 18h01 p.m. and Zero hours. Practically all the occurrences related to the traffic and drugs use were given in the Central Sector, with exception of the registers of imprisoned children for traffic, whose raised occurrence more was observed in the Sector East of the city. We evidenced that some of the homicides have the drug as predispose factor. About the income and the schooling, we verified that 56% of the inhabitants received between 1 and 3 minimum wages and 30% have only Element School. It was observed that in the majority of the quarters with greater purchasing power and high level of schooling (Superior Education), in this cases haven t occurrence of homicides. Another side, in the quarters of low schooling and income, we observed registered occurrences, however of low intensity. One evidenced that in 38% of the quarters of Uberlândia, the tax of homicides identified was of 1 the 38/100,000 inhabitants. Therefore, we considered that urban violence, the homicides, Public Security situation in Brazil needs an urgent State intervention because the consequences verified it has been carry problems to the Brazilian population, innumerable problems.